The first world empire: Portugal, war and military revolution - Carvalhal, Hélder; Murteira, André; Jesus, Roger Lee de (Warfare and History, 2021)
"This book offers a comprehensive overview of the early modern military history of Portugal and its possessions in Africa, the Americas, and Asia from the perspective of the military revolution historiographical debate. The existence of a military revolution in the early modern period has been much debated in international historiography, and this volume fills a significant gap in its relation to the history of Portugal and its overseas empire. It examines different forms of military change in specifically Portuguese case studies but also adopts a global perspective through the analysis of different contexts and episodes in Africa, the Americas, and Asia. Contributors explore whether there is evidence of what could be defined as aspects of a military revolution or whether other explanatory models are needed to account for different forms of military change. In this way, it offers the reader a variety of perspectives that contribute to the debate over the applicability of the military revolution concept to Portugal and its empire during the early modern period. Broken down into four thematic parts and broad in both chronological and geographical scope, the book deepens our understanding of the art of warfare in Portugal and its empire and demonstrates how the military revolution debate can be used to examine military change in a global perspective. This is an essential text for scholars and students of military history, military architecture, global history, Asian history, and the history of Iberian empires."--